Analysis Of Evizia Effectiveness In The Process Of Recording And Processing Doctors' Medical Services Towards The Automation Of The Financial Reporting Process Of Jih Hospital, Yogyakarta - Adira Valda Khakim; Nurfauziah (Cita konsultindo, 2026)
This study aims to analyze the effectiveness of the Evizia Information System in recording and managing doctors' medical services and its impact on the automation of financial reporting processes at JIH Hospital, Yogyakarta. Using a qualitative research method based on the DeLone and McLean Information System Success Model, data were collected through interviews and observation.. The findings reveal that Evizia has improved the efficiency of recording processes and data accuracy, replacing manual methods with digital solutions; however, it still faces issues such as limited automation, unstable internet connectivity, and lack of formal user training. Despite being regularly used and integrated into hospital workflows, user satisfaction remains moderate due to incomplete system functionalities and reliance on IT support. These results suggest that while Evizia contributes positively to transparency and time efficiency, further system development is necessary to enhance decision-making capabilities and fully realize its strategic benefits for hospital financial management. The study implies that investing in infrastructure, training, and feature integration is crucial for optimizing hospital information systems.